What Is the “Optimal” Target Mismatch Criteria for Acute Ischemic Stroke? - Chen, Chushuang; Parsons, Mark W.; Levi, Christopher R.; Spratt, Neil J.; Lin, Longting; Kleinig, Timothy; Butcher, Kenneth; Cheng, Xin; Dong, Qiang; O'Brien, Billy; Avivi, Richard I.; Krause, Martin; et al. (Frontiers in Neurology, 2021)
We aimed to compare Perfusion Imaging Mismatch (PIM) and Clinical Core Mismatch (CCM) criteria in ischemic stroke patients to identify the effect of these criteria on selected patient population characteristics and clinical outcomes. Patients from the INternational Stroke Perfusion Imaging REgistry (INSPIRE) who received reperfusion therapy, had pre-treatment multimodal CT, 24-hour imaging, and 3 month outcomes were analyzed. Patients were divided into 3 cohorts: endovascular thrombectomy (EVT), intravenous thrombolysis alone with large vessel occlusion (IVT-LVO), and intravenous thrombolysis alone without LVO (IVT-nonLVO). Patients were classified using 6 separate mismatch criteria: PIM - using 3 different measures to define the perfusion deficit (Delay Time, Tmax, or Mean Transit Time); or CCM - mismatch between age-adjusted National Institutes of Health Stroke Scale and CT Perfusion core, defined as relative cerebral blood flow <30% within the perfusion deficit defined in three ways (as above). We assessed the eligibility rate for each mismatch criterion and its ability to identify patients likely to respond to treatment. There were 994 patients eligible for this study. PIM with delay time (PIM-DT) had the highest inclusion rate for both EVT (82.7%) and IVT-LVO (79.5%) cohorts. In PIM positive patients who received EVT, recanalization was strongly associated with achieving an excellent outcome at 90-days (e.g. PIM-DT: mRS 0-1, adjusted OR 4.27, P=0.005), whereas there was no such association between reperfusion and an excellent outcome with any of the CCM criteria (all p>0.05). Notably, in IVT-LVO cohort, 58.2% of the PIM-DT positive patients achieved an excellent outcome compared with 31.0% in non-mismatch patients following successful recanalization (P=0.006). Conclusion: PIM-DT was the optimal mismatch criterion in large vessel occlusion patients, combining a high eligibility rate with better clinical response to reperfusion. No mismatch criterion was useful to identify patients who are most likely response to reperfusion in non-large vessel occlusion patients.